Cross-infection in epidemics spread by carriers. Issue 2 (3rd April 2018) - Lefèvre, Claude; Simon, Matthieu
ABSTRACT: A block-structured transient Markov process is introduced to describe an epidemic spreading within two linked populations, of carriers and susceptibles. The epidemic terminates as soon as there are no more carriers or susceptibles present in the population. Our purpose is to determine the distribution of the final susceptible and carrier states, and of any integral path for the susceptible process. The transient epidemic state is also briefly discussed. Then, the model is extended to allow the recovery of infected individuals. Finally, several particular models, some known, are used for illustration.